2020
DOI: 10.1080/14733285.2020.1778638
|View full text |Cite
|
Sign up to set email alerts
|

Developmental spaces? Developmental Psychology and urban geographies of youth in sub-Saharan Africa

Abstract: While urban geographies play a critical role in shaping youth development, existing literature has focused primarily on the ways in which young people use, navigate and shape cities. This has overlooked the depth and complexity of Africa's urban youth crisis. This paper introduces a new analytic framework, based on principles of Developmental Psychology, outlining the four critical psychosocial processes of building foundations, building blocks, building support structures and building aspirations that young p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…Our study showed that age was correlated with participants' commitment to join the program. Supports our result, another study showed that young adults have more conscience regarding health issues and more capable to manage their health problems (50). Those qualities enable young adults in this study to participate more significantly to prevent health problems.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that age was correlated with participants' commitment to join the program. Supports our result, another study showed that young adults have more conscience regarding health issues and more capable to manage their health problems (50). Those qualities enable young adults in this study to participate more significantly to prevent health problems.…”
Section: Discussionsupporting
confidence: 89%